Recurrent abdominal pain as an indicator of epilepsy: A Case Report (Journal of Psychiatrists' Association of Nepal, 2024)
Abdominal epilepsy is a rare reason why children experience stomach discomfort repeatedly. The haziness of these symptoms makes it very likely to misdiagnose a patient. Paroxysmal episodes of abdominal pain accompanied by neurological symptoms like vertigo, post-ictal sleepiness or tiredness, specific electroencephalographic abnormalities, and a relief in symptoms after antiepileptic drug therapy all help to diagnose abdominal epilepsy. We discuss a fifteen-year-old boy who frequently complains of stomach pain. The reason of the pain was not found despite a detailed evaluation and thorough inquiry. We reached to a diagnosis of abdominal epilepsy based on detail history. Treatment with oxcarbazepine helped to reduce the pain.